Educational Environment as the Basis for the Formation of Universal Competencies of Students - A. V. Churakova (Открытое образование (Москва))
The purpose of the study. The legislation of the Russian Federation describes education as a single purposeful process of education and training. At the same time, education rightly stands before learning, in the first place, at all levels of education. The importance of personal development in educational institutions of higher education is spelled out in various regulatory documents of the federal level. The legislator defines education as a systemic process that is one for understanding by teaching staff in the field of education; therefore, the active development of the educational environment has become one of the primary tasks for universities, regardless of their departmental affiliation. The effectiveness of modern education depends on the educational environment in which the holistic educational process is carried out. Moreover, according to the federal state educational standards of higher education, not professional, but universal competencies come to the fore, providing opportunities for flexible human strategies (education, profession, personal and social strategies) in a competitive environment that accelerates changes in the labor market. It is the environment that is the basis for the formation of universal competencies of students. However, in the practice of Russian educational institutions of higher education, the potential of the educational process is not included in the formation of universal graduate competencies. The purpose of the presented paper is to analyze the current state of the personal development environment of educational institutions of higher education as the basis for the formation of universal competencies of students.Materials and methods of research. The research was based on scientific and methodological literature that reveals the essence of the educational space in higher educational institutions, studies the issues of personal development in educational institutions of higher education and the components of the personal development environment in the formation of universal competencies of students. When studying these sources on the problem under consideration, methods of theoretical analysis and synthesis, their abstraction and concretization were used. The methodological basis of the research was complex and technological approaches as the most important components of the educational environment, systemic and environmental approaches as the basis of the educational function of the university in modeling the educational environment with the expectation of profiling training, as well as an activity approach associated with the activity nature of the formation of universal competencies of students.Results. As a result of the research, the historical aspect of the formation of the concept of “educational environment” has been studied and its formulation has been clarified, the differences between this concept and the concept of “nurturing environment” have been identified and the possibilities of the educational environment in the formation of universal competencies of students have been characterized.Conclusion. The theoretical analysis carried out and the conclusions of the study on the problem under consideration can be used in scientific and pedagogical activities when considering the issues of regulating the personal development process in educational institutions of higher education, thereby improving the quality of the holistic educational process. It is important to analyze the possibilities of the personal development environment of educational institutions of higher education in the practical formation of universal competencies of students.